Time to broaden pharmacological treatment of cardiovascular disorders with physiological dimensions of Adropin - Akhlaq, Sana (Journal of the Pakistan Medical Association, 2025)
Adropin, an emerging substance hailed for its heart-protective potential, presents a promising avenue for combating cardiovascular ailments. The current narrative review was planned to underscore its link with metabolic syndrome and its role in preventing ischemic heart disease, accentuating its multifaceted impact on metabolism and cardiac wellbeing. Mechanistically, it operates through diverse pathways, including modulation of endothelial nitric oxide synthase, anti-apoptotic properties, and regulation of pyruvate dehydrogenase phosphorylation to boost cellular energy production and mitochondrial function. Furthermore, its interactions with cellular receptors, signalling cascades and metabolic regulators unveil its prowess in mitigating cardiovascular risks and enhancing glycaemic control. To transition adropin from bench to bedside, rigorous human trials are imperative, encompassing dose optimisation, long-term safety assessments, and exploration of genetic influences. Inclusive research targeting diverse populations, especially high-risk cohorts, is advocated to unravel its full therapeutic potential. Interdisciplinary collaboration is pivotal for unravelling its mechanisms as a targeted therapy for cardiovascular disorders. Key Words: Adropin, ENHO protein, Human protein, Rat protein, Myocardial ischemia, Coronary artery disease, Pyruvates, Pyruvic acid, Nitric oxide, Mitochondria, Apoptosis, Therapeutic, Risk factors, Collateral circulation, Homeostasis.